Metode Pengajaran Gus Yusuf Chudlori Pada Hadis-Hadis Yang Berkaitan Dengan Pendidikan Anak Dalam Kitab Ayyuha Al-Walad - Faridah, Faridatul Miladiyah (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2023)
Gus Yusuf is a religious scholar specializing in the field of Sufism. He extensively studies Sufi texts, one of which is the book Ayyuha al-Walad by Imam Ghazali. Although there have been many studies discussing or analyzing hadiths on child education, this research focuses specifically on one book, namely Ayyuha al-Walad. In the book Ayyuha al-Walad, many hadiths on education can be found, but it is also possible to find hadiths related to Sufism or education with a Sufi flavor. This is because the purpose of the book is to provide advice from Imam Ghazali to his students (who, after years of learning, still do not know what truly benefits them, so they ask their teacher to write down everything that should be followed in order to benefit in the hereafter). The author has selected hadiths that are relevant to the theme of education. This study utilizes both manual and digital library research methods. The data for the study includes the book Ayyuha al-Walad as the main reference, as well as commentaries on Ayyuha al-Walad and other foundational texts. The digital data sources include platforms such as Maktabah Syamilah, Jami' Kutubuttis'ah, the internet, and others. Gus Yusuf not only employs classical research methods but also utilizes modern methods, such as social media, as a means of preaching. This allows the general public to participate in the study without having to attend the gatherings in person. The study of the book Ayyuha al-Walad conducted by Gus Yusuf has received an extraordinary response and has been viewed thousands of times within a short period.